Enriched lithospheric mantle keel below the Scottish margin of the North Atlantic Craton : evidence from the Palaeoproterozoic Scourie Dyke Swarm and mantle xenoliths. - Hughes, H.S.R.; McDonald, I.; Goodenough, K.M.; Ciborowski, T.J.R.; Kerr, A.C.; Davies, J.H.F.L.; Selby, D. (Precambrian Research, 2014)
The Lewisian Gneiss Complex of NW Scotland represents the eastern margin of the North Atlantic Craton. It comprises mid-late Archaean tonalite-trondhjemite-granodiorite gneisses that were metamorphosed and deformed during the Late-Archaean and Palaeoproterozoic. A major swarm of mafic-ultramafic dykes, the Scourie Dyke Swarm, was intruded at ca. 2.4–2.3 Ga during a period of extension that can be correlated across the North Atlantic Craton. The majority of dykes are doleritic, with volumetrically minor picrite and olivine gabbro suites. New major and trace element geochemical data and Re-Os isotopes indicate that the Scourie Dyke Swarm was not solely derived from a ‘typical’ asthenospheric mantle source region. The geochemical signatures of the dykes show significant negative Nb, Ta and Ti anomalies, coupled with enrichment in Th, Light Rare Earth Elements and other large ion lithophile elements. These features cannot be reproduced by simple contamination of asthenospheric sources with Lewisian granulite-facies crust. Instead they are a feature of the mantle source that produced the Scourie Dykes and may have developed during Archaean subduction episodes. Spinel lherzolite mantle xenoliths from the Isle of Lewis offer direct insight into the lithospheric mantle below this region. They display similar geochemical ‘enrichments’ and ‘depletions’ observed in the Scourie Dykes and the magma source is thus considered to reside primarily in the sub-continental lithospheric mantle (SCLM), with some potential contribution from asthenospheric melts. Platinum Group Element geochemistry and trace element modelling indicate that the dolerite dykes were formed by moderate (<15%) partial melting of the source, whilst higher degrees of partial melting led to the formation of picritic and olivine gabbro suites. Magma production was triggered by significant crustal and lithospheric extension, causing both asthenospheric and substantial lithospheric melting.